Temperature Depended Role of Shigella flexneri Invasion Plasmid on the Interaction with Acanthamoeba castellanii - Amir Saeed; David Johansson; Gunnar Sandström; Hadi Abd (International Journal of Microbiology)
Shigella flexneri is a Gram-negative bacterium causing the diarrhoeal disease shigellosis in humans. The virulence genes required for invasion are clustered on a large 220 kb plasmid encoding type three secretion system (TTSS) apparatus and virulence factors such as adhesions and invasion plasmid antigens (Ipa). The bacterium is transmitted by contaminated food, water, or from person to person. Acanthamoebae are free-living amoebae (FLA) which are found in diverse environments and isolated from various water sources. Different bacteria interact differently with FLA since Francisella tularensis, Vibrio cholerae, Shigella sonnei, and S. dysenteriae are able to grow inside A. castellanii. In contrast, Pseudomonas aeruginosa induces both necrosis and apoptosis to kill A. castellanii. The aim of this study is to examine the role of invasion plasmid of S. flexneri on the interaction with A. castellanii at two different temperatures. A. castellanii in the absence or presence of wild type, IpaB mutant, or plasmid-cured strain S. flexneri was cultured at 30∘C and 37∘C and the interaction was analysed by viable count of both bacteria and amoebae, electron microscopy, flow cytometry, and statistical analysis. The outcome of the interaction was depended on the temperature since the growth of A. castellanii was inhibited at 30∘C, and A. castellanii was killed by invasion plasmid mediated necrosis at 37∘C.